2013
DOI: 10.1061/(asce)is.1943-555x.0000097
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Ductile Iron Pipes. I: Characterization of External Corrosion Patterns

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…As noted in the conclusions of the Kleiner et al (2013), no compelling evidence was found that soil samples would improve the ability to predict corrosion pit properties in any significant or consistent manner. Consequently, soil properties are not considered in the current discussion of sampling and statistical inference on pipe condition.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…As noted in the conclusions of the Kleiner et al (2013), no compelling evidence was found that soil samples would improve the ability to predict corrosion pit properties in any significant or consistent manner. Consequently, soil properties are not considered in the current discussion of sampling and statistical inference on pipe condition.…”
Section: Introductionmentioning
confidence: 90%
“…The appropriate underlying population in the current context is that of rings in a pipe, as described in Kleiner et al (2013). Simple random sampling of say, n samples, would entail the selection of n sample rings whose locations are determined randomly (with assumed uniform distribution) along the entire pipe.…”
Section: Samplingmentioning
confidence: 99%
See 3 more Smart Citations